Fault protection solutions appropriately proposed for ungrounded low-voltage AC microgrids: Review and proposals. (August 2017) - Bui, Duong Minh; Chen, Shi-Lin
Abstract: This paper investigates transient and dynamic characteristics and proposes available fault protection solutions for ungrounded low-voltage (LV) AC microgrids. Transient characteristics of the ungrounded LVAC microgrid are surveyed through fault tests and transition tests of the microgrid operation between the grid-connected and the islanded operation modes. Additionally, dynamic behaviours of the ungrounded LVAC microgrid are surveyed through motor starting tests and different load conditions. Simulation results under transient and dynamic operation situations are used to evaluate available fault protection solutions proposed for the ungrounded low-voltage AC microgrids.